Improvement of early mortality in single‐unit cord blood transplantation for Japanese adults from 1998 to 2017. Issue 4 (2nd January 2020) - Konuma, Takaaki; Kanda, Junya; Inamoto, Yoshihiro; Hayashi, Hiromi; Kobayashi, Shinichi; Uchida, Naoyuki; Sugio, Yasuhiro; Tanaka, Masatsugu; Kobayashi, Hikaru; Kouzai, Yasushi; Takahashi, Satoshi; Eto, Tetsuya; et al.
Abstract: The major limitation of cord blood transplantation (CBT) for adults remains the delayed hematopoietic recovery and higher incidence of graft failure, which result in a higher risk of early mortality in CBT. We evaluated early overall survival (OS), non‐relapse mortality (NRM), neutrophil engraftment, acute graft‐vs‐host disease, and cause of early death among 9678 adult patients who received single‐unit CBT in Japan between 1998 and 2017. The probability of OS at 100 days was 64.4%, 71.7%, and 78.9% for the periods 1998 to 2007, 2008 to 2012, and 2013 to 2017, respectively ( P < .001). The cumulative incidences of NRM at 100 days during the same period were 28.3%, 20.8%, and 14.6%, respectively ( P < .001). The cumulative incidences of neutrophil engraftment were also improved during the same period ( P < .001). The most common cause of death within 100 days after CBT was bacterial infection in 1998 to 2007 and primary disease in the latter two time periods. Across the three time periods, the proportions of deaths from bacterial and fungal infection, graft failure, hemorrhage, sinusoidal obstructive syndrome, and organ failure decreased in a stepwise fashion. Landmark analysis of OS and NRM after 100 days showed that OS did not change over time in the multivariate analysis. Our registry‐based data demonstrated a significant improvement of early OS after CBT for adults over the past 20 years. The landmark analysis suggested that improvement of early mortality could lead to an improvement of long‐term OS after CBT.